2014
DOI: 10.1039/c3dt52269e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Li/OR phosphinidenoid complexes: on the evidence for intramolecular O–Li donation and the effect of cation encapsulation

Abstract: Synthesis of phosphinite complexes 12-14a-c, 15a and 16a was achieved via reaction of transient Li/Cl phosphinidenoid complexes 6-10, prepared from dichloro(organo)phosphane complexes [(OC)5M{RPCl2}] 1-5 (1,6: R = CPh3, 2,7: R = C5Me5, 3-5, 8-10: R = CH(SiMe3)2, 1-3, 6-8: M = W, 9: M = Mo, 10: M = Cr), with different alcohols 11a-c (a: R = allyl, b: R = methyl, c: R = isopropyl). Deprotonation of complexes 12b, 13b with MeLi or (t)BuLi in the presence of two equivalents of 12-crown-4 led to the selective forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
(9 reference statements)
2
20
0
Order By: Relevance
“…We observed that the chemical shift and the coupling constant ( 1 J ) magnitude was dependent on the organic substituent at the nitrogen center. Consistent with the trend observed for phosphinite complexes, a trend for high‐field‐shifted resonances was observed with the increase of steric demand at the nitrogen center (Me> i Pr> t Bu). The observed resonance signals of complexes 3 a – e are shifted downfield compared to the previously reported aminophosphane complexes, which were obtained by a thermal reaction of a 7‐phosphanorbornadiene complex or a 2 H ‐azaphosphirene complex with amines.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…We observed that the chemical shift and the coupling constant ( 1 J ) magnitude was dependent on the organic substituent at the nitrogen center. Consistent with the trend observed for phosphinite complexes, a trend for high‐field‐shifted resonances was observed with the increase of steric demand at the nitrogen center (Me> i Pr> t Bu). The observed resonance signals of complexes 3 a – e are shifted downfield compared to the previously reported aminophosphane complexes, which were obtained by a thermal reaction of a 7‐phosphanorbornadiene complex or a 2 H ‐azaphosphirene complex with amines.…”
Section: Resultssupporting
confidence: 83%
“…), which has attracted considerable attention owing to the versatile construction of useful building blocks . A similar insertion reaction of Li/Cl phosphinidenoid complexes into the O−H bonds of alcohol derivatives to yield phosphinite complexes was reported recently . In contrast to extensive investigations on carbenoid insertions into N−H bonds, similar reactions of silylenoid compounds are much less investigated and are completely unknown for M/X phosphinidenoid complexes.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations